Developing Efl Speaking Materials for Students of Islamic in Education Department, IAI Hamzanwadi Pancor - Rizal, Syamsul (Indonesian Journal of Education Research and Technology (IJERT), 2023)
This research and development (R&D) is conducted to develop EFL speaking materials for the first semester students of Islamic in Education Program. The speaking materials were developed based on needs assessment which was conducted in Islamic in Education Program of IAI Hamzanwadi Pancor. The procedure used to develop the materials was adapted from the model developed by Hyland (2003) which consists of seven stages i.e. needs assessment, developing the materials, experts and lectures validation, revision, try out, revision, and final product. The subjects of the tryout were the students of first semester C in the 2022/2023 academic year. Forty-two students were selected from this semester by stratified random sampling. The instruments used in needs assessment were questionnaires for the English lectures and the students, an interview guide for the English lectures, and field notes. A validation form was given to the experts and the English lectures to judge and give comments on the developed materials. The instruments used in the tryout were questionnaires for the students, an evaluation form for the lecture, field notes, and students’ tasks. The result of the analysis revealed that the developed speaking materials were appropriate for the first semester students in terms of clarity of the contents, attractiveness, speed of delivery, and level of difficulty. The data from the result of the needs analysis shows most of the students agree to develop EFL speaking materials, to include list of vocabulary in the EFL speaking materials they are learning, to include grammar review in the future EFL speaking materials, to clarify the content of the materials in the explanation, and to arrange the materials according to the degree of its difficulty. From the try-out of the developed materials the data shows the applicability of the developed materials in helping the students to achieve the mastery of speaking skills and language components. Besides, the materials were practical to implement and effective for teaching speaking skills. The final product consisting of a teacher’s guide, a speaking workbook which had 12 units for the first semester. The units were taken from any relevant references.